2014
DOI: 10.1186/1471-2164-15-168
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Caenorhabditis eleganssperm transcriptome and proteome

Abstract: BackgroundAlthough sperm is transcriptionally and translationally quiescent, complex populations of RNAs, including mRNAs and non-coding RNAs, exist in sperm. Previous microarray analysis of germ cell mutants identified hundreds of sperm genes in Caenorhabditis elegans. To take a more comprehensive view on C. elegans sperm genes, here, we isolate highly pure sperm cells and employ high-throughput technologies to obtain sperm transcriptome and proteome.ResultsFirst, sperm transcriptome consists of considerable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 56 publications
6
67
0
Order By: Relevance
“…As a result, low abundance lncRNAs expressed in only a fraction of cells are difficult to detect by RNA-seq of whole worm bodies (56). Supporting this hypothesis, a transcriptome of worm sperm revealed and validated 8 novel lncRNAs that the whole-body gene expression profile generated by the modENCODE Consortium failed to identify (57). Similarly, our muscle transcriptome revealed 461 novel transcripts with high confidence.…”
Section: Discussionmentioning
confidence: 88%
“…As a result, low abundance lncRNAs expressed in only a fraction of cells are difficult to detect by RNA-seq of whole worm bodies (56). Supporting this hypothesis, a transcriptome of worm sperm revealed and validated 8 novel lncRNAs that the whole-body gene expression profile generated by the modENCODE Consortium failed to identify (57). Similarly, our muscle transcriptome revealed 461 novel transcripts with high confidence.…”
Section: Discussionmentioning
confidence: 88%
“…Microarray studies indicated sperm expression (Reinke et al 2004), while later transcriptome and proteome profiling did not (Ma et al 2014). RT-PCR from fem-3(q23) mutant hermaphrodites (producing only sperm) amplified a prominent spe-47 product, whereas only a very faint product was amplified from fem-1(hc17) mutant animals, which produce only oocytes (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Only two genes with novel mutations were found in the map region for hc198: Y23H5A.4 and F28B3.6 (Table 1 and Figure 1). Microarray data suggested that Y23H5A.4 is upregulated in sperm (Reinke et al 2000(Reinke et al , 2004, while transcriptome profiling showed that F28B3.6 is expressed in sperm (Ma et al 2014) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the proteome covers a considerable amount of the transcriptome with 59% of all identified KO IDs. Using mass spectrometry, Bai et al [53] identified about 40% of the genes in Aspergillus flavus , while [52] show for the sperm cells of Caenorhabditis elegans that 1080 of 2511 (approx. 30%) protein annotations overlap with the transcriptome.…”
Section: Resultsmentioning
confidence: 99%